2021
DOI: 10.22159/ijpps.2021v13i4.37980
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Genus Tinospora in Wound Healing: A Review

Abstract: Genus Tinospora has been used in traditional medicine throughout various parts of Asia, particularly in India, China, Thailand, Malaysia and Cambodia. Its ethnomedicinal uses include treatment for fever, cold, oral ulcer, headaches, diarrhoea, diabetes, digestive disorder and rheumatoid arthritis. Some of its ethnomedicinal uses have been justified via scientific studies, include antidiabetic, antioxidant, anti-inflammatory and antimicrobial effects. Recently, several studies have been initiated to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Over recent years, the wound healing ability of TC on different wound models has been explored both orally and topically. These studies indicated that TC has a positive effect on wound healing [14]. However, its effect on diabetic WH activity has not been investigated thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Over recent years, the wound healing ability of TC on different wound models has been explored both orally and topically. These studies indicated that TC has a positive effect on wound healing [14]. However, its effect on diabetic WH activity has not been investigated thus far.…”
Section: Introductionmentioning
confidence: 99%